When the Great Power Gets a Vote: The Effects of Great Power Electoral Interventions on Election Results. - LEVIN, DOV H. (International Studies Quarterly, 2016)
What are the electoral consequences of attempts by great powers to intervene in a partisan manner in another country's elections? Great powers frequently deploy partisan electoral interventions as a major foreign policy tool. For example, the U.S. and the USSR/Russia have intervened in one of every nine competitive national level executive elections between 1946 and 2000. However, scant scholarly research has been conducted about their effects on the election results in the target. I argue that such interventions usually significantly increase the electoral chances of the aided candidate and that overt interventions are more effective than covert interventions. I then test these hypotheses utilizing a new, original dataset of all U.S. and USSR/Russian partisan electoral interventions between 1946 and 2000. I find strong support for both arguments.